VHDL for logic synthesis - Rushton, Andrew (Chichester, U.K. : John Wiley & Sons, 2011)
'Macrocycles: Construction, Chemistry and Nanotechnology Applications is an essential introduction this important class of molecules and describes how to synthesise them, their chemistry, how they can be used as nanotechnology building blocks, and their applications'--
Includes bibliographical references and index.
Keywords: VHDL (Computer hardware description language).; Logic design -- Data processing; Computer-aided design